EDUKASI MANAJEMEN STRES PADA PENDERITA GASTRITIS DI WILAYAH GEMBONG 4 KELURAHAN KAPASAN KECAMATAN SIMOKERTO - Orizani, Chindy Maria; Susila, Wahyu Dini Candra; Tjokro, Silvia Haniwidjaya (Community Development in Health Journal, 2025)
Introduction & Aim: Gastritis is a stomach disease that is very disturbing because in addition to causing pain, gastritis can also trigger distress. Likewise, distress can also cause gastritis recurrence. To overcome distress, it can be done with psychosocial health support. Mental health and psychosocial support in this service offers relaxation techniques including deep breath relaxation, progressive muscle relaxation, and 5-finger hypnosis. This is because relaxation techniques are considered to have the benefit of reducing pain reactions caused by gastritis recurrence, besides that this relaxation technique is also considered to reduce the level of distress in gastritis sufferers so that gastritis recurrence can be prevented. This community service aims to reduce the level of psychological distress in gastritis sufferers in the Gembong number 4 area of Surabaya. Method of Activity: Community service uses lecture, discussion and demonstration strategies. This activity also conducted a pre-post-test to evaluate the benefits of the exercise. This activity was attended by 21 participants with gastritis complaints. Initial screening and evaluation of respondents' psychological distress data were collected through the DASS-21 questionnaire. Results: The measurement results showed differences in psychological distress in gastritis sufferers before and after community service was carried out. Discussion: The results of community service activities on education and stress management are beneficial for people with gastritis in the Gembong Gang 4 area of ​​Surabaya. This condition can be the beginning of changes related to the management of mental health conditions.